Engaging leaders at two hierarchical levels in organizational health interventions: Insights from the intervention team. Issue 4 (25th September 2018) - Karanika-Murray, Maria; Gkiontsi, Dimitra; Baguley, Thom
Abstract : Purpose: Although visible leader support is an essential ingredient for successful organizational health interventions, knowledge on how leaders at different hierarchical levels engage with interventions is underdeveloped. The purpose of this paper is to explore leader engagement by drawing from the experiences of the intervention team. Design/methodology/approach: Data from semi-structured interviews with the team responsible for implementing an organizational health intervention in two large UK organizations were used to examine how leaders at strategic (senior management) and operational (line managers) positions engaged with the intervention. Findings: Thematic analysis uncovered 6 themes and 16 sub-themes covering the leaders' initial reactions to the intervention, barriers to leader engagement, ways in which the intervention team dealt with these barriers, factors facilitating and factors accelerating leader engagement, and differences in engagement between leadership levels. Research limitations/implications: This study can inform research into the conditions for optimizing leader engagement in organizational health interventions and beyond. Insights also emerged on the roles of leaders at different hierarchical levels and the value of perspective taking for intervention implementation. Practical implications: Recommendations for bolstering the engagement of leaders in interventions are offered, that apply to all leaders or separately to leaders at strategic or operational levels. Originality/value: The experiences of the intervention team who sought to engage leaders at different organizational levels to support the intervention are invaluable. Understanding how leader engagement can be maximized can better equip intervention teams for delivering successful interventions.